Microfinance institutions' operational self-sufficiency in sub-Saharan Africa: Empirical evidence - Laxmi Remer; Hanna Kattilakoski (International Journal of Corporate Social Responsibility (JCSR), 2021)
The topic of financial sustainability in microfinance institutions has become more important as an increasing number of Microfinance Institutions (MFIs) seek operational self-sufficiency, which translates into financial sustainability. This study aims to identify factors that drive operational self-sufficiency in microfinance institutions. To accomplish this, 416 MFIs in sub-Saharan Africa are studied and several drivers for operational self-sufficiency are empirically analyzed. Results indicate that these drivers are return on assets, and the ratios total expenses/assets and financial revenues/assets. The results imply that MFIs should encourage cost-management measures. They also reveal that there may not be a significant tradeoff in self-sufficiency and outreach. These findings will enable microfinance institutions worldwide to sharpen their institutional capabilities to achieve operational self-sufficiency and also provide policymakers with more focused tools to assist industry development.
Keywords: 650; MFI; Microfinance institution; Operational self-sufficiency; Financial sustainability; Outreach; Financial inclusion; Africa